Strategi Pencegahan COVID-19: Peningkatan Imunitas Tubuh Melalui Edukasi Konsumsi Teh Kombucha - Akhmal, Faisal; Fendy Prasetyawan; Yuneka Saristiana; Ratna Mildawati; Anis Akhwan Dhafin (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
The COVID-19 pandemic, triggered by the coronavirus 2 (SARS-CoV-2), demands a rapid and effective response to protect the global community. This article discusses prevention strategies with a focus on boosting the body's immunity through education and the consumption of kombucha tea. COVID-19 varies in symptoms and impacts, requiring a holistic approach. Kombucha tea, a result of fermenting sweet tea with a SCOBY, provides high nutrition and health benefits, particularly in strengthening the immune system. Community outreach activities are conducted to disseminate information to healthcare professionals and students, discussing the benefits of kombucha tea in enhancing immunity during the pandemic. The methods of these activities involve preparation, implementation of educational sessions, and participant satisfaction evaluations. Research findings highlight the potential of kombucha tea, especially its antioxidant and anti-inflammatory compounds, in enhancing the body's resilience against SARS-CoV-2. This strategy can be reinforced by emphasizing overall healthy lifestyles. Despite its promise, challenges in implementation require effective education and cross-sector collaboration. The conclusion emphasizes the importance of a holistic approach and education in building the foundation of public health amid the pandemic.